A rainbow flash glaze, preparation method and application in ceramics
By adding specific components and modified materials to the ceramic glaze, the problems of single flash effect and reduced performance of existing ceramic products are solved, and ceramic tile products with rainbow flash effect, good wear resistance and gloss are achieved.
Patent Information
- Application Number
- CN202411242725.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-05
AI Technical Summary
Most of the existing flash ceramic products have only a single flash effect, and cannot form rainbow flash ceramic tile products with excellent decorative effects. At the same time, the production process can easily lead to a reduction in the performance of ceramic tile.
A rainbow glaze glaze is used, including potassium feldspar, alumina, barium carbonate, diamond powder, alumina, talc, calcined zinc oxide and water-washed kaolin, and mixed with glaze dry particles to enhance the glaze glaze and wear resistance by modifying zircon sand and modified silicon nitride.
The rainbow glitter effect of ceramic tiles is achieved, good wear resistance and gloss are maintained, and the service life of the product is extended.
Smart Images

Figure BDA0005029768050000111 
Figure BDA0005029768050000121 
Figure BDA0005029768050000122
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic glazes and relates to a rainbow flash glaze, a preparation method and application in ceramics. Background Art
[0002] As people continue to pursue quality of life and space aesthetics, ceramic tiles, as the main body of home decoration, have developed a wide range of colors and textures. Among the many types of ceramic tiles, imitation marble ceramic tiles are a more mainstream ceramic tile product with rich and colorful surface processes, such as imitation marble ceramic tiles that simulate the flashing effect of special natural stones.
[0003] Most of the existing glitter ceramic products only have a single glitter effect, and therefore cannot form rainbow glitter ceramic tile products with excellent decorative effects. At the same time, the existing production process is likely to cause changes in the performance of ceramic tiles, resulting in a reduction in other properties of the tiles such as glossiness and hardness. Summary of the invention
[0004] The purpose of the present invention is to provide a rainbow glitter glaze, a preparation method and application in ceramics. The ceramic tile prepared by the present invention has a rainbow glitter effect, good wear resistance and glossiness.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A rainbow flash glaze, comprising the following components by weight: 30-45 parts of potassium feldspar, 5-7 parts of alumina, 10-15 parts of barium carbonate, 2-5 parts of diamond powder, 2-3 parts of sodium feldspar, 9-12 parts of aluminum oxide, 4-7 parts of talc, 8-15 parts of calcined zinc oxide, 5-8 parts of washed kaolin, 15-20 parts of flash dry particles and 5-10 parts of water;
[0007] The flash dry particles include the following raw materials in parts by weight: 30 to 35 parts of modified zircon sand, 5 to 8 parts of diopside, 20 to 25 parts of rhodonite, 10 to 18 parts of modified silicon nitride, 4 to 7 parts of fluorite powder, 5 to 8 parts of spodumene and 3 to 6 parts of calcium phosphate.
[0008] As a preferred technical solution of the present invention, the preparation process of the modified silicon nitride is as follows:
[0009] S21, pickling the silicon nitride with a sulfuric acid solution, and drying with hot air to obtain pretreated silicon nitride;
[0010] S22, by weight, dissolving 10 to 15 parts of cobalt nitrate hexahydrate in 50 to 55 parts of water, and then adding 20 to 30 parts of pretreated silicon nitride and stirring well to obtain a precursor mixture;
[0011] S23, stirring the precursor mixture at 170-200° C. for 5-8 h, cooling naturally to room temperature, centrifuging, washing with ethanol, and drying in a vacuum drying oven at 120° C. to obtain a dry solid;
[0012] S24, calcining the dried solid at 650-720° C. for 2-3 h in a nitrogen environment, naturally cooling to 200-240° C. for 5-7 h after calcination, and then cooling to room temperature to obtain silicon nitride with cobalt oxide loaded on the surface;
[0013] S25, grinding 20 to 25 parts of silicon nitride with cobalt oxide loaded on the surface and 13 to 18 parts of rutile in a ball mill at a speed of 400 r / min for 4 to 5 hours, and sieving through 200 to 300 meshes to prepare the modified silicon nitride.
[0014] As a preferred technical solution of the present invention, the preparation process of the modified zircon sand is as follows:
[0015] S31, calcining zircon sand at 1200-1230° C., cooling to room temperature, adding the zircon sand to a ball mill, adding water, and ball milling at a speed of 400 r / min for 3-4 hours, then passing through a 100-200 mesh sieve, and drying to obtain zircon sand fine powder;
[0016] S32. Add 12 to 17 parts of zircon sand powder and 100 to 130 parts of stearic acid, by weight, to 200 to 250 parts of ethanol, mix them by ultrasonic for 15 to 20 minutes, heat to 50 to 60° C., stir for 1 to 2 hours, and then remove the solvent by vacuum distillation to obtain the modified zircon sand.
[0017] As a preferred technical solution of the present invention, in step S21, the sulfuric acid solution is a sulfuric acid aqueous solution with a mass fraction of 15%.
[0018] As a preferred technical solution of the present invention, in step S31, the water is 8-10% of the mass of the zircon sand.
[0019] A method for preparing a rainbow glitter glaze comprises the following steps:
[0020] The components of the flash dry particles are fully stirred and mixed according to the weight proportions of the formula, heated and calcined at 1550-1630° C. for 3-5 hours, then naturally cooled to room temperature, and then ground in a ball mill at a speed of 500 r / min for 2-4 hours to obtain a mixture; the mixture is then fully mixed with the remaining components of the rainbow flash glaze, and the speed is maintained to continue to be mixed and ball-milled in the ball mill for 2-4 hours, and passed through a 300-350 mesh sieve to prepare the rainbow flash glaze.
[0021] As a preferred technical solution of the present invention, the rotation speed during stirring is 700-800 r / min.
[0022] An application of a rainbow flash glaze in ceramics, wherein the rainbow flash glaze is applied to prepare ceramic tiles, comprising the following steps:
[0023] S81, pressing the green body, and then drying it at 160-200°C;
[0024] S82: Apply base glaze on the surface of the dried body through bell jar glazing process. The glaze water density is controlled at 1.0-1.4g / mL during glazing, and the glaze amount is 650-720g / m 2 ;
[0025] S83, spray ink on the bottom glaze layer by intelligent inkjet printing to obtain an effect pattern and form a pattern layer, apply rainbow flash glaze on the surface of the pattern layer by bell jar glazing process, and the glazing amount of the rainbow flash glaze is 600-700g / m 2 ;
[0026] S84, drying and firing the brick blanks glazed in step S83, and then polishing and waxing them to obtain ceramic tiles with rainbow flash effect.
[0027] As a preferred technical solution of the present invention, in step S84, the firing temperature is 1170-1230° C. and the firing time is 1-1.5 h.
[0028] Silicon nitride exists in tiny forms in the glaze. When light shines on these particles, scattering occurs, resulting in a sparkling effect. Silicon nitride particles change the surface roughness of the glaze, causing the glaze to produce more reflection and scattering under light, thereby enhancing the sparkling effect. At the same time, silicon nitride has good chemical stability at high temperatures, which helps the glaze maintain the stability of its composition and properties during the firing process, thereby facilitating the formation of a uniform sparkling effect. Silicon nitride has a high refractive index and reflectivity. These optical properties may make the glaze produce a brighter and more sparkling effect under light. When light passes through a glaze layer containing silicon nitride particles, interference and diffraction occur, further enhancing the sparkling effect of the glaze.
[0029] Silicon nitride has a porous structure. Acid washing can remove surface pollutants, improve the surface purity of silicon nitride, increase its surface potential and improve surface performance. Silicon nitride with surface loaded cobalt oxide is obtained by impregnation and calcination with metal salt solution. Cobalt oxide is a color pigment with strong high-temperature stability. It can form a variety of colors in ceramic glazes. By loading cobalt oxide on the surface, the color of the glaze can be precisely controlled to make it richer and more diverse, which is conducive to forming a rainbow flash effect. Cobalt oxide particles can absorb oxygen in the glaze and form a crystallization-like effect on the glaze, making the glaze smoother and more shiny. The improvement in gloss can further enhance the flash effect. The coloring ability and gloss enhancement effect of cobalt oxide can be combined with the high gloss of silicon nitride to create a more unique and dazzling flash effect.
[0030] Rutile has good optical properties and chemical stability, and can significantly increase the transparency and glossiness of the glaze layer. After being mixed with silicon nitride with cobalt oxide loaded on the surface, rutile can form a transparent film, which produces rainbow colors through the thin film interference effect, thereby adjusting the sparkling color and optical properties of the glaze.
[0031] Silicon nitride, rutile and cobalt oxide work together in the glaze to produce complex color changes through the principles of color superposition and light interference. Silicon nitride and rutile use the opacity effect and optical properties to cause light to be reflected and scattered multiple times in the glaze layer, forming a rainbow-like flash effect, while cobalt oxide acts as a base color or auxiliary color, enhancing the richness and layering of this color change. Together, the three enhance the rainbow flash effect of ceramic glazes.
[0032] In the present invention, zircon sand is firstly calcined to further optimize the crystal structure of zircon sand and make the particles closer together, thereby improving the refraction and scattering effects caused by optical fiber irradiation; then, zircon sand is modified by stearic acid. Zircon sand has high hardness. After being modified by stearic acid, its hardness is further maintained. Adding the modified zircon sand to the glaze can improve the hardness of the glaze surface, make the ceramic products more wear-resistant, and thus extend the service life of the flashing ceramic products; stearic acid, as a surfactant, has good lubricity and dispersibility. In the process of glaze preparation, stearic acid-modified zircon sand can improve the compatibility and dispersibility of filler and glaze matrix, reduce the agglomeration between zircon sand particles, make the glaze more uniform and delicate, and help the glaze surface to form a smooth and flat surface during the firing process, thereby improving The gloss of the glaze; at the same time, stearic acid modification helps to adjust the melting behavior of zircon sand in the glaze. When the glaze is sintered to prepare the glaze layer, due to the stearic acid modification, stearic acid can form a lubricating layer between the zircon sand particles to reduce friction resistance. Therefore, the zircon sand can flow and spread better between the glazes, thereby filling the tiny depressions and unevenness on the ceramic surface to form a smoother and continuous glaze layer. This smooth glaze layer can reflect more light, thereby improving the gloss of the glaze; at the same time, due to the good lubrication and dispersing effect of stearic acid, it can reduce the bubbles and impurity defects generated during the glaze sintering process, thereby improving the gloss of the glaze, helping to form a purer and smoother glaze, thereby increasing the reflectivity of the glaze. The higher the reflectivity, the brighter the glaze looks, thereby further enhancing the rainbow sparkle effect of the glaze.
[0033] Beneficial effects of the present invention:
[0034] In the present invention, a glaze base composed of potassium feldspar, alumina, barium carbonate, diamond powder, sodium feldspar, aluminum oxide, talc, calcined zinc oxide and washed kaolin is mixed with flash dry particles to prepare a ceramic glaze with a rainbow flash effect, and a ceramic tile with a rainbow flash effect is prepared by sintering. The rhodonite in the flash dry particles has a glass luster and can form a crystal structure with modified zircon sand and modified boron nitride during the sintering process. These crystals have different refractive indices from the glass phase in the glaze. When light is irradiated on the glaze surface, the light refracted between different crystals will form interference colors, thereby generating rainbow flash; at the same time, the melting rearrangement between different filler particles can help enhance the rainbow flash effect; at the same time, fluorite powder, diopside, spodumene and calcium phosphate are used as fluxes to improve the stability of the ceramic glaze.
[0035] The tiny particles or crystal structures of various fillers present in the glaze of the present invention scatter and refract the light, further enhancing the rainbow flash effect of the glaze. When the light is irradiated to the glaze, part of the light is scattered in all directions through the glaze to form scattered light; the other part of the light enters the interior of the glaze layer through refraction, and then is emitted from the glaze after multiple reflections and refractions, forming rich color changes. DETAILED DESCRIPTION
[0036] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0037] Example 1
[0038] Preparation of modified silicon nitride:
[0039] S21, pickling the silicon nitride with a sulfuric acid solution having a mass fraction of 15%, and drying with hot air to obtain pretreated silicon nitride;
[0040] S22, by weight, dissolving 10 parts of cobalt nitrate hexahydrate in 50 parts of water, and then adding 20 parts of pretreated silicon nitride and stirring well to obtain a precursor mixture;
[0041] S23, stirring the precursor mixture at 170° C. for 5 h, cooling naturally to room temperature, centrifuging, washing with ethanol, and drying in a vacuum drying oven at 120° C. to obtain a dry solid;
[0042] S24, calcining the dried solid at 650° C. for 2 h in a nitrogen environment, naturally cooling to 200° C. for 5 h after calcination, and then cooling to room temperature to obtain silicon nitride with cobalt oxide loaded on the surface;
[0043] S25. Grind 20 parts of silicon nitride with cobalt oxide loaded on the surface and 13 parts of rutile in a ball mill at a speed of 400 r / min for 4 h, and sieve through 200 mesh to prepare modified silicon nitride.
[0044] Preparation of modified zircon sand:
[0045] S31, calcining zircon sand at 1200° C., cooling to room temperature, adding the zircon sand into a ball mill, adding 8% water by mass of the zircon sand, ball milling at a speed of 400 r / min for 3 hours, passing through a 100 mesh sieve, and drying to obtain zircon sand fine powder;
[0046] S32. By weight, 12 parts of zircon sand powder and 100 parts of stearic acid are added to 200 parts of ethanol, and the mixture is ultrasonically mixed for 15 minutes. The mixture is heated to 50° C. and stirred for 1 hour, and then the solvent is removed by vacuum distillation to obtain modified zircon sand.
[0047] Preparation of Rainbow Glitter Glaze:
[0048] According to weight, 30 parts of modified zircon sand, 5 parts of diopside, 20 parts of rhodonite, 10 parts of modified silicon nitride, 4 parts of fluorite powder, 1 part of spodumene and 3 parts of calcium phosphate are fully stirred and mixed at a speed of 700 r / min, heated and calcined at 1550°C for 3 hours, then naturally cooled to room temperature, and then ground in a ball mill at a speed of 500 r / min for 2 hours to obtain a flash dry particle mixture; then 30 parts of potassium feldspar, 5 parts of alumina, 10 parts of barium carbonate, 2 parts of diamond powder, 2 parts of sodium feldspar, 9 parts of aluminum oxide, 4 parts of talc, 8 parts of calcined zinc oxide, 5 parts of washed kaolin, and 5 parts of water are added and fully mixed, the speed is maintained and the mixture is continued to be mixed and ball-milled in a ball mill for 2 hours, and passed through a 300-mesh sieve to prepare a rainbow flash glaze.
[0049] The rainbow flash glaze is used to prepare ceramic tiles, comprising the following steps:
[0050] S81, pressing the green body, and then drying it at 160°C;
[0051] S82: Apply base glaze on the surface of the dried body by bell glazing process. The glaze water density is controlled at 1.0g / mL and the glaze amount is 650g / m 2 ;
[0052] S83, ink is sprayed on the bottom glaze layer by intelligent inkjet printing to obtain an effect pattern and form a pattern layer, and rainbow flash glaze is applied on the surface of the pattern layer by bell jar glazing process, and the glazing amount of the rainbow flash glaze is 600g / m 2 ;
[0053] S84, drying the glazed bricks in step S83, firing them at 1170°C for 1 hour, and then polishing and waxing them to obtain ceramic tiles with rainbow glitter effect.
[0054] Example 2
[0055] Preparation of modified silicon nitride:
[0056] S21, pickling the silicon nitride with a sulfuric acid solution having a mass fraction of 15%, and drying with hot air to obtain pretreated silicon nitride;
[0057] S22, dissolving 13 parts of cobalt nitrate hexahydrate in 53 parts of water by weight, and then adding 25 parts of pretreated silicon nitride and stirring well to obtain a precursor mixture;
[0058] S23, stirring the precursor mixture at 180° C. for 6 h, cooling naturally to room temperature, centrifuging, washing with ethanol, and drying in a vacuum drying oven at 120° C. to obtain a dry solid;
[0059] S24, calcining the dried solid at 680° C. for 2.5 h in a nitrogen environment, and naturally cooling to 220° C. for 6 h after the calcination to obtain silicon nitride with cobalt oxide loaded on the surface;
[0060] S25. Grind 23 parts of silicon nitride with cobalt oxide loaded on the surface and 15 parts of rutile in a ball mill at a speed of 400 r / min for 4.5 h, and sieve through 250 mesh to prepare modified silicon nitride.
[0061] Preparation of modified zircon sand:
[0062] S31, calcining zircon sand at 1220° C., cooling to room temperature, adding the zircon sand to a ball mill, adding water which accounts for 9% of the mass of the zircon sand, ball milling at a speed of 400 r / min for 3.5 hours, passing through a 150 mesh sieve, and drying to obtain zircon sand fine powder;
[0063] S32. By weight, 14 parts of zircon sand powder and 110 parts of stearic acid are added to 230 parts of ethanol, and the mixture is ultrasonically mixed for 17 minutes. The mixture is heated to 55° C. and stirred for 1.5 hours, and then the solvent is removed by vacuum distillation to obtain modified zircon sand.
[0064] Preparation of Rainbow Glitter Glaze:
[0065] According to weight, 33 parts of modified zircon sand, 7 parts of diopside, 23 parts of rhodonite, 15 parts of modified silicon nitride, 6 parts of fluorite powder, 7 parts of spodumene and 5 parts of calcium phosphate are fully stirred and mixed at a speed of 750r / min, heated and calcined at 1600℃ for 4h, then naturally cooled to room temperature, and then ground by a ball mill at a speed of 500r / min for 3h to obtain a flash dry particle mixture; then 38 parts of potassium feldspar, 6 parts of alumina, 13 parts of barium carbonate, 4 parts of diamond powder, 2.5 parts of sodium feldspar, 10 parts of aluminum oxide, 5 parts of talc, 11 parts of calcined zinc oxide, 7 parts of washed kaolin and 8 parts of water are added and fully mixed, the speed is maintained and the mixture is continued to be mixed and ball-milled by the ball mill for 3h, and passed through a 330-mesh sieve to prepare a rainbow flash glaze.
[0066] The rainbow flash glaze is used to prepare ceramic tiles, comprising the following steps:
[0067] S81, pressing the green body, and then drying it at 180°C;
[0068] S82, apply the base glaze on the surface of the dried body through the bell jar glazing process, the glaze water density is controlled at 1.2g / ml during glazing, and the glaze amount is 680g / m 2 ;
[0069] S83, spray ink on the bottom glaze layer by intelligent inkjet printing to obtain an effect pattern and form a pattern layer, apply rainbow flash glaze on the surface of the pattern layer by bell jar glazing process, and the glazing amount of the rainbow flash glaze is 650g / m 2 ;
[0070] S84, drying and firing the brick blanks glazed in step S83, and then polishing and waxing them to obtain ceramic tiles with rainbow flash effect.
[0071] As a preferred technical solution of the present invention, in step S84, the firing temperature is 1200° C. and the firing time is 1.3 h.
[0072] Example 3
[0073] Preparation of modified silicon nitride:
[0074] S21, pickling the silicon nitride with a sulfuric acid solution having a mass fraction of 15%, and drying with hot air to obtain pretreated silicon nitride;
[0075] S22, dissolving 15 parts of cobalt nitrate hexahydrate in 55 parts of water by weight, and then adding 30 parts of pretreated silicon nitride and stirring well to obtain a precursor mixture;
[0076] S23, stirring the precursor mixture at 200° C. for 8 h, cooling naturally to room temperature, centrifuging, washing with ethanol, and drying in a vacuum drying oven at 120° C. to obtain a dry solid;
[0077] S24, calcining the dried solid at 720° C. for 3 h in a nitrogen environment, and naturally cooling to 240° C. for 7 h after the calcination to obtain silicon nitride with cobalt oxide loaded on the surface;
[0078] S25. Grind 25 parts of silicon nitride with cobalt oxide loaded on its surface and 18 parts of rutile in a ball mill at a speed of 400 r / min for 5 h, and sieve through 300 mesh to prepare modified silicon nitride.
[0079] Preparation of modified zircon sand:
[0080] S31, calcining zircon sand at 1230° C., cooling to room temperature, adding the zircon sand to a ball mill, adding water (10% by weight of the zircon sand), ball milling at a speed of 400 r / min for 4 hours, passing through a 200-mesh sieve, and drying to obtain zircon sand powder;
[0081] S32. By weight, 17 parts of zircon sand powder and 130 parts of stearic acid are added to 250 parts of ethanol, mixed by ultrasonic for 20 minutes, heated to 60°C, stirred for 2 hours, and then distilled under reduced pressure to remove the solvent, thereby obtaining modified zircon sand.
[0082] Preparation of Rainbow Glitter Glaze:
[0083] According to weight, 35 parts of modified zircon sand, 8 parts of diopside, 25 parts of rhodonite, 18 parts of modified silicon nitride, 7 parts of fluorite powder, 8 parts of spodumene and 6 parts of calcium phosphate are fully stirred and mixed at a speed of 800 r / min, heated and calcined at 1630°C for 5 hours, then naturally cooled to room temperature, and then ground by a ball mill at a speed of 500 r / min for 4 hours to obtain a flash dry particle mixture; then 45 parts of potassium feldspar, 7 parts of alumina, 15 parts of barium carbonate, 5 parts of diamond powder, 3 parts of sodium feldspar, 12 parts of aluminum oxide, 7 parts of talc, 15 parts of calcined zinc oxide, 8 parts of washed kaolin and 10 parts of water are added and fully mixed, the speed is maintained and the mixture is continued to be mixed and ball-milled by the ball mill for 4 hours, and passed through a 350-mesh sieve to prepare a rainbow flash glaze.
[0084] The rainbow flash glaze is used to prepare ceramic tiles, comprising the following steps:
[0085] S81, pressing the green body, and then drying it at 200°C;
[0086] S82, apply the base glaze on the surface of the dried body through the bell jar glazing process, the glaze water density is controlled at 1.4g / mL, and the glaze amount is 720g / m 2 ;
[0087] S83, ink is sprayed on the bottom glaze layer by intelligent inkjet printing to obtain an effect pattern and form a pattern layer, and rainbow flash glaze is applied on the surface of the pattern layer by bell jar glazing process, and the glazing amount of the rainbow flash glaze is 700g / m 2 ;
[0088] S84, drying and firing the brick blanks glazed in step S83, and then polishing and waxing them to obtain ceramic tiles with rainbow flash effect.
[0089] As a preferred technical solution of the present invention, in step S84, the firing temperature is 1230° C. and the firing time is 1.5 h.
[0090] Comparative Example 1
[0091] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, when preparing the modified silicon nitride, cobalt nitrate hexahydrate treatment is not performed, steps S22-S24 are not performed, and the remaining operations are the same.
[0092] Comparative Example 2
[0093] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the modified silicon nitride is not mixed with rutile for ball milling, and the other operations are the same.
[0094] Comparative Example 3
[0095] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the silicon nitride is not modified, and the other operations are the same.
[0096] Comparative Example 4
[0097] The difference between Comparative Example 4 and Example 1 is that the zircon sand in Comparative Example 4 is not modified with stearic acid, and the other operations are the same.
[0098] Comparative Example 5
[0099] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, no rhodonite is added to the flash dry particles, and the other operations are the same.
[0100] Performance Test:
[0101] 1. Abrasion resistance: According to the abrasion resistance test method of glazed tiles in GB / T3810.7-2015 ceramic tile test method, the tile abrasion resistance tester produced by Shenzhen Opuri Testing Equipment Co., Ltd. is used for testing;
[0102] 2. Glossiness: Use 3NH gloss meter NHG60 to measure glossiness. The results are as follows:
[0103] Table 1:
[0104]
[0105]
[0106] 3. Glaze effect, brick surface effect: Observe with naked eyes to see if there are impurities and carbon bubbles on the brick surface, and whether the brick surface pattern is clear. The results are shown in Table 2:
[0107] Table 2:
[0108]
[0109]
[0110] According to the above data, the data of the embodiments are better than those of the comparative examples. It can be seen from comparative examples 1-3 that the flash effect, glossiness and wear resistance of comparative example 3 are worse than those of comparative examples 1-2, indicating that the boron nitride modified by surface loading of cobalt oxide and rutile in the present invention can effectively improve the glossiness and glaze effect of ceramic tiles. It can be seen from comparative example 4 and example 1 that zircon sand modified by stearic acid can help improve the glossiness and flash effect of zircon sand in ceramic glazes due to its good lubricity and dispersibility. According to comparative example 5 and example 1, it can be seen that no rhodonite is added in comparative example 5, and the flash effect is poor. Therefore, the rainbow flash glaze prepared by the present invention can be used to prepare ceramic tiles with good rainbow flash effect, and has good wear resistance and glossiness.
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A rainbow glitter glaze, characterized in that: The invention comprises the following components by weight: 30-45 parts of potassium feldspar, 5-7 parts of alumina, 10-15 parts of barium carbonate, 2-5 parts of diamond powder, 2-3 parts of sodium feldspar, 9-12 parts of aluminum oxide, 4-7 parts of talc, 8-15 parts of calcined zinc oxide, 5-8 parts of washed kaolin, 15-20 parts of flash dry particles and 5-10 parts of water; The flash dry particles include the following raw materials in parts by weight: 30-35 parts of modified zircon sand, 5-8 parts of diopside, 20-25 parts of rhodonite, 10-18 parts of modified silicon nitride, 4-7 parts of fluorite powder, 5-8 parts of spodumene and 3-6 parts of calcium phosphate; The preparation process of the modified silicon nitride is as follows: S21, pickling the silicon nitride with a sulfuric acid solution, and drying with hot air to obtain pretreated silicon nitride; S22, by weight, dissolving 10 to 15 parts of cobalt nitrate hexahydrate in 50 to 55 parts of water, and then adding 20 to 30 parts of pretreated silicon nitride and stirring well to obtain a precursor mixture; S23, stirring the precursor mixture at 170-200° C. for 5-8 h, cooling naturally to room temperature, centrifuging, washing with ethanol, and drying in a vacuum drying oven at 120° C. to obtain a dry solid; S24, calcining the dried solid at 650-720° C. for 2-3 hours under a nitrogen environment, and naturally cooling to 200-240° C. for 5-7 hours after the calcination, to obtain silicon nitride with cobalt oxide loaded on the surface; S25, grinding 20-25 parts of silicon nitride with cobalt oxide loaded on the surface and 13-18 parts of rutile in a ball mill at a speed of 400 r / min for 4-5 hours, and sieving through 200-300 meshes to prepare the modified silicon nitride.
2. The rainbow flash glaze according to claim 1, characterized in that: The preparation process of the modified zircon sand is as follows: S31, calcining zircon sand at 1200-1230°C, cooling to room temperature, adding it to a ball mill, adding water, and ball milling at a speed of 400 r / min for 3-4 hours, then passing through a 100-200 mesh sieve, and drying to obtain zircon sand fine powder; S32. By weight, add 12 to 17 parts of zircon sand powder and 100 to 130 parts of stearic acid to 200 to 250 parts of ethanol, mix them by ultrasonic for 15 to 20 minutes, heat to 50 to 60° C., stir for 1 to 2 hours, and then remove the solvent by reduced pressure distillation to obtain the modified zircon sand.
3. The rainbow flash glaze according to claim 1, characterized in that: In step S21, the sulfuric acid solution is a sulfuric acid aqueous solution with a mass fraction of 15%.
4. The rainbow flash glaze according to claim 2, characterized in that: In step S31, the water is 8-10% of the mass of the zircon sand.
5. A method for preparing the rainbow flash glaze according to any one of claims 1 to 4, characterized in that: The process includes the following steps: According to the weight proportion of the formula, the components of the flash dry particles are fully stirred and mixed, heated and calcined at 1550-1630° C. for 3-5 hours, then naturally cooled to room temperature, and then ground in a ball mill at a speed of 500 r / min for 2-4 hours to obtain a mixture; then the mixture is fully mixed with the remaining components of the rainbow flash glaze, and the speed is maintained to continue to be mixed and ball-milled in the ball mill for 2-4 hours, and passed through a 300-350 mesh sieve to prepare the rainbow flash glaze.
6. The method for preparing the rainbow flash glaze according to claim 5, characterized in that: The rotation speed during stirring is 700-800 r / min.
7. An application of the rainbow flash glaze according to any one of claims 1 to 4 in ceramics, characterized in that: The rainbow flash glaze is used to prepare ceramic tiles, comprising the following steps: S81, pressing the green body, and then drying it at 160-200°C; S82: Apply base glaze on the surface of the dried body through bell jar glazing process. The glaze water density is controlled at 1.0~1.4g / mL during glazing, and the glaze amount is 650~720g / m 2 ; S83, spray ink on the bottom glaze layer by intelligent inkjet printing to obtain an effect pattern and form a pattern layer, apply rainbow flash glaze on the surface of the pattern layer by bell jar glazing process, and the glazing amount of the rainbow flash glaze is 600~700g / m 2 ; S84, drying and firing the brick blanks glazed in step S83, and then polishing and waxing them to obtain ceramic tiles with rainbow flash effect.
8. The use of the rainbow flash glaze in ceramics according to claim 7, characterized in that: In step S84, the firing temperature is 1170-1230° C. and the firing time is 1-1.5 h.
Citation Information
Patent Citations
Natural granite-imitated ceramic tile with wear-resistant effect and preparation method thereof
CN112250309A
Diamond glittering glaze, glittering marble tile and preparation process of glittering marble tile
CN116002978A